Je časné zahájení dialyzační léčby u nemocných s CKD výhodné? Studie IDEAL - Cooper, B. A; Branley, P; Bulfone, L; Collins, J. F; Craig, J. C; Fraenkel, M. B; Harris, A; Johnson, D. W; Kesselhut, J; Li, J. J; Luxton, G; Pilmore, A; et al. (Postgraduální nefrologie, 2010)
In clinical practice, there is considerable variation in the timing of the initiation of maintenance dialysis for patients with stage V chronic kidney disease, with a worldwide trend toward early initiation. In this study, conducted at 32 centers in Australia and New Zealand, we examined whether the timing of the initiation of maintenance dialysis influenced survival among patients with chronic kidney disease. METHODS: We randomly assigned patients 18 years of age or older with progressive chronic kidney disease and an estimated glomerular filtration rate (GFR) between 10.0 and 15.0 ml per minute per 1.73 m2 of body-surface area (calculated with the use of the Cockcroft-Gault equation) to planned initiation of dialysis when the estimated GFR was 10.0 to 14.0 ml per minute (early start) or when the estimated GFR was 5.0 to 7.0 ml per minute (late start). The primary outcome was death from any cause. RESULTS: Between July 2000 and November 2008, a total of 828 adults (mean age, 60.4 years; 542 men and 286 women; 355 with diabetes) underwent randomization, with a median time to the initiation of dialysis of 1.80 months (95% confidence interval [CI], 1.60 to 2.23) in the early-start group and 7.40 months (95% CI, 6.23 to 8.27) in the late-start group. A total of 75.9% of the patients in the late-start group initiated dialysis when the estimated GFR was above the target of 7.0 ml per minute, owing to the development of symptoms. During a median follow-up period of 3.59 years, 152 of 404 patients in the early-start group (37.6%) and 155 of 424 in the late-start group (36.6%) died (hazard ratio with early initiation, 1.04; 95% CI, 0.83 to 1.30; P=0.75). There was no significant difference between the groups in the frequency of adverse events (cardiovascular events, infections, or complications of dialysis). CONCLUSIONS: In this study, planned early initiation of dialysis in patients with stage V chronic kidney disease was not associated with an improvement in survival or clinical outcomes. (Funded by the National Health and Medical Research Council of Australia and others; Australian New Zealand Clinical Trials Registry number, 12609000266268.)
Keywords: kardiovaskulární nemoci; Uremia; infekce; Time Factors; lidé středního věku; Renal Dialysis; lidé; časové faktory; Adult; Middle Aged; dospělí; proporcionální rizikové modely; Kaplan-Meier Estimate; chronické selhání ledvin; Proportional Hazards Models; Female; hodnoty glomerulární filtrace; financování organizované; Male; randomizované kontrolované studie jako téma; ženské pohlaví; kvalita života; Humans; mužské pohlaví; Quality of Life; Kaplanův-Meierův odhad; Randomized Controlled Trials as Topic; Financing, Organized; Infections; dialýza ledvin; uremie; Glomerular Filtration Rate; Cardiovascular Diseases; Kidney Failure, Chronic